Cyanoacrylate Glue Versus Absorbable Tacks in Mesh Fixation for Laparoscopic Extraperitoneal Inguinal Hernia Repair: A Randomized Controlled Trial. Issue 3 (June 2021) - Issa, Michael; Tacey, Mark; Geraghty, Joshua; Das, Atandrila; Dhir, Arun; Mori, Krinal; To, Henry
Abstract : Background: Cyanoacrylate glue (Glubran 2) is a synthetic adhesive mesh fixation material. Its utility is being evaluated in laparoscopic total extraperitoneal (TEP) inguinal hernia repair (IHR). A multicentre randomized controlled trial was performed comparing Glubran 2 to standard of care absorbable tacks, particularly assessing chronic postoperative inguinal pain and its effects. Materials and Methods: Patients undergoing elective TEP IHR at 2 centers from 2017 to 2019 were randomly assigned to Glubran 2 or absorbable tack mesh fixation, and followed for 6 months. All other aspects of surgery and aftercare remained the same. Surgeons documented operative and fixation time, and the placement of fixation on standardized diagrams. Via a questionnaire, aspects of inguinal pain were evaluated before surgery, and at various time-points postoperatively over 6 months. Postoperative clinical factors were also collected. Results: A total of 106 operative sides were randomized to either glue (51) or tack (55) mesh fixation over a 14-month period. Similar median operative times between tack (83.0 min) and glue fixation (75.0 min) were observed. There were no significant surgical complications or observed hernia recurrences in either group. There was no significant difference in pain scores between the 2 groups at all time-points after analysis through mixed effects modeling. Temporal pain profiles over time were also similar. Totally, 55% of patients in the glue group had returned to work within 2 weeks of surgery. There was no increase in complications or pain scores despite regular lateral fixation of glue in these patients. Conclusion: Adding to known data, we observed no significant difference in postoperative pain, demonstrating that cyanoacrylate glue is a viable and safe alternative fixation method to absorbable tacks in laparoscopic TEP IHR. As secondary outcomes, cyanoacrylate glue permits some patients to return to work early, and we observed regular lateral mesh glue fixation without increased pain or complications. Abstract : Supplemental Digital Content is available in the text.